Impact of phagostimulants on effectiveness of OMRI‐listed insecticides used for control of spotted‐wing drosophila (Drosophila suzukii Matsumura). (22nd February 2019) - Roubos, Craig R.; Gautam, Bal K.; Fanning, Philip D.; Van Timmeren, Steven; Spies, Janine; Liburd, Oscar E.; Isaacs, Rufus; Curry, Shane; Little, Brian A.; Sial, Ashfaq A.
Abstract: Spotted‐wing drosophila, Drosophila suzukii Matsumura, is an invasive pest in the United States that causes considerable damage to fruit crops. It is responsible for many millions of dollars of revenue loss. The female D. suzukii has a heavily sclerotized ovipositor and can lay eggs in ripening or ripe fruit. The arrival of this invasive species has disrupted existing integrated pest management programmes, and growers rely on repeated insecticide applications to protect fruit. Organic growers have few chemical control options, and their reliance on spinosad increases the risk of developing insecticide resistance. We hypothesized that combining phagostimulants with insecticides would increase insecticide efficacy by prompting flies to spend more time in contact with residues. Therefore, the objective of this study was to evaluate the effectiveness of sucrose and the yeast Saccharomyces cerevisiae as phagostimulants in combination with organic biopesticides against D. suzukii in blueberries. Adding sucrose with or without yeast did not improve insecticide efficacy in terms of adult fly mortality or fruit infestation. Spinosad was very effective in all experiments, and for this product, there is little room for improvement. The phagostimulants had no effect on residual activity of any insecticide. The addition of sucrose with or without yeast did not improve the effectiveness of organic insecticides for D. suzukii . Concentrations of these phagostimulants in our experiments (0.36%) may have been too low to elicit a response. Further research is recommended to test different types and concentrations of phagostimulants.